A Ratchet for Closed Pipes: Asymmetric-Configuration Role on Unidirectional Circulatory Flows - Lihang Bai; Zhang Liu; Yulong Ji; Shuai Wang (Energies)
Unidirectional pulsating heat pipes (PHPs) have been extensively investigated. However, a comprehensive understanding of the mechanism is still lacking. In this study, we analyze the unidirectional flow (distinct from thermosyphon) in closed PHP loops and reveal that the combined effect of the diameter variation and pressure distribution leads to a stable circulatory flow. Analogous to the Carnot thermodynamic cycle, a flow dynamical cycle along the loop is proposed to determine the highest momentum increment rate at the limit of the pressures and tube cross-sections. Furthermore, an effective pressure cycle considering friction resistance is introduced to elucidate the balance between fluid momentum increase and decrease. Experiments with glass PHP tubes are conducted to visualize fluid movements and characterize unidirectional flow PHPs accurately. The results confirm that varying-diameter PHP significantly promotes the circulatory flow, highlighting its potential for PHP development.